Pengaruh Inflasi, Impor dan Ekspor Terhadap Pertumbuhan Ekonomi di Indonesia - Nur Afifah Nanda Riyanti; Ulfa Zulhaeni Batigin; Rokhimah Batigin; Fatima Az-zahra Wairooy (Prodi Ekonomi Syariah IAIN Sorong, 2024)
This study analyzes the impact of inflation, imports, and exports on economic growth in Indonesia using secondary data and a linear regression model. The dependent variable is economic growth, measured by the growth rate of Gross Domestic Product (GDP), while the independent variables include inflation, imports, and exports. The analysis shows that inflation does not have a significant impact on economic growth. Exports have a positive and significant impact, while imports do not have a significant impact. These findings are consistent with previous research showing that exports positively affect economic growth, while inflation and imports are not significant in the short term. Policies that support exports should be strengthened to enhance Indonesia's economic growth, alongside effective inflation management and selective import strategies.